Study guides

☆☆

Q: Simplify 2x plus 6 2y plus 3y?

Write your answer...

Submit

Still have questions?

Related questions

5x+2x-3y+y = (5+2)x+(-3+1)y = 7x - 2y

(7x-3y) + (2x+5y) = 9x+2y

the simplest form of 5x + 3y +2x - 6y is 7x-3y

3y2 - 2y + 6xy - 4x = y(3y - 2) + 2x(3y - 2) = (y + 2x)*(3y - 2)

2x + 3y + 4x + 9y = 2x + 4x + 3y + 9y = 6x + 12y which can be simplified to 6(x + 2y)

4x-2y

4x+3y-2x+y 4x-2x+3y+y 2x+4y Taking out 2 common 2(x+2y) Hence the required answer is 2(x+2y)

2x+3y=40-2x+2y=20Since 2x does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting 2x from both sides.3y=-2xDivide each term in the equation by 3.(3y)/(3)=-(2x)/(3)Simplify the left-hand side of the equation by canceling the common terms.y=-(2x)/(3)if you were solving for x It would be x=-(3y)/2

3y+2z

3x + y

10x - 5y + 2x - 3y = 12x - 8y

4x + 3y - 2x - 7y2x - 4y

People also asked